상관관계분석을 이용한 시공능력평가 제도의 실증적 고찰 - 정근채; Jeong, Keun Chae (한국건설관리학회 논문집, 19(2), 2018)
The system to appraise the execution capabilities of construction companies had been began as the Construction Contract Restriction System in 1958, was changed as the Construction Subcontract Restriction System in 1961, and finally has been operated as the Appraisal and Public Announcement of Execution Capacity (APAEC) from 1996. The APAEC system has been utilized as a firm and unique tool for assessing the execution capacities of construction companies despite many problems and continuous system changes. In spite of numerous studies to improve the APAEC system, however, efforts to analyze the system from the empirical point of view were insufficient. In this study, we analyze the status of APAEC system through analyzing correlations among assessment results of the APAEC, earned values of construction works, construction management performance indexes, and macroeconomic indexes for the past 10 years from 2007 to 2016. As a result of the analysis, it was found that Appraisal Value of Execution Capacity (AVEC) is excessively inflated in engineering and landscaping areas compared to Earned Value of Construction Work (EVCW) and the correlations between the AVECs and EVECs are not high in the areas of engineering, industrial equipment, and landscaping. In addition, technical appraisal values are excessively inflated in engineering and landscaping areas and correlations between AVEC and its components are high in the areas of engineering & building, industrial equipment, and large companies, but low in the areas of engineering, building, landscaping, and small and medium companies. Finally, the concentration of the AVEC is intensifying more and more and the concentration deteriorates construction management performance indexes and macroeconomic indexes. If we continuously improve the APAEC system based on the implications derived in this study, the APAEC system will be able to maintain it's position of a firm and unique means to access the execution capacities of construction companies. 기업의 시공능력을 평가하기 위한 노력은 지난 1958년 공사청부제한제도로 시작되어 1961년 공사도급제한제도를 거쳐 1996년 시공능력 평가 및 공시로 변경된 채 현재에 이르고 있다. 시공능력 평가 및 공시 제도는 그동안 많은 문제점 및 그에 따른 제도개선에도 불구하고 건설업체의 공사수행 역량을 평가하기 위한 확고하고 유일한 수단으로 활용되어 있다. 그러나 그동안 수행되었던 시공능력 평가 및 공시 제도의 개선을 위한 다수의 연구에도 불구하고 본 제도를 실증적 관점에서 분석하고자 하는 노력은 부족했다. 이에 본 연구에서는 지난 2007년부터 2016년까지의 10년간의 시공능력 평가 결과, 건설공사실적, 건설업 경영관리 지표, 거시경제 지표에 대한 상관관계분석을 통해 시공능력 평가 및 공시 제도의 현황을 분석하고 그에 따른 시사점을 도출하였다. 분석결과, 시공능력 평가액은 토목과 조경 분야에서 건설공사실적에 비해 지나치게 부풀려져 있으며, 토목, 산업설비, 조경 분야에서 시공능력 평가액과 건설공사실적 간에 상관관계가 높지 않음을 알 수 있었다. 또한, 토목과 조경 분야의 기술능력평가액이 지나치게 부풀려져 있으며, 토건과 산업설비 그리고 규모가 큰 기업은 시공능력 평가액과 세부 평가액들 간의 상관관계가 높았으나, 토목, 건축과 조경 분야와 규모가 작은 기업은 그 상관관계가 높지 않았다. 마지막으로 시공능력 평가액의 집중이 점점 심화되고 있으며, 시공능력 평가액 집중도와 건설업 경영관리 지표와 및 거시지표와의 상관관계 분석 결과, 시공능력 평가액의 집중은 건설업 경영관리 지표와 거시지표를 악화시키고 있음을 알 수 있었다. 본 연구에서 도출된 시공능력 평가 및 공시 제도에 대한 시사점을 바탕으로 대안을 수립하여 본 제도에 대한 개선을 수행한다면, 건설업체의 공사수행 역량을 평가하기 위한 확고하고 유일한 수단으로서의 지위를 향후에도 지속적으로 유지할 수 있을 것이다.